Structural Health Monitoring Based Predictive Model of Concrete Bridge - Khairul Anuar, Shahid; Norhaiza, Ghazali; Mohd Arif, Sulaiman (2014)
Reinforced concrete bridge is widely used nowadays in most modern small bridges because of in situ reinforced concrete construction which has the great advantage and simplicity. However, bridges possess high risk attack by corrosion by chloride ingress due to de-icing salt. The salt contains high level of chloride. The presence of chloride ions in concrete will cause corrosion initiation to reinforcement bar embedded inside the concrete. Thus, it will leads to severe structural damaged. Reinforced concrete bridge need to be manage effectively for better allocation of resources and serve based on it intended design.